Enhancing students' fluency in thinking: An inquiry-based approach with bell ringer exams - Ratraikit, Aekkalak; Hemtasin, Chulida; Thongsuk, Tawan; Payoungkiattikun, Wisarut (Asian Journal of Contemporary Education, 2025)
This action research aimed to enhance fluency thinking in the Year 9 Science and Technology course on Genetics by integrating bell ringer exams with inquiry-based learning. The study's objectives were to achieve an 80% pass rate in fluency thinking and to assess student satisfaction with this pedagogical approach. The sample comprised 20 Year 9 students from the first semester of the 2022 academic year. The research utilized ten learning plans, a fluency thinking test, an interview form, and a satisfaction questionnaire. The study followed an action research model implemented in two cycles. Data were analyzed using averages, standard deviations, and percentages. The findings revealed significant improvement in students' fluency thinking, with 85% and 100% passing the criteria in the first and second cycles, respectively. Additionally, students reported high levels of satisfaction with the learning activities. This study demonstrates that combining bell ringer exams with inquiry-based learning is effective in fostering critical thinking and engagement in scientific subjects. The approach proved particularly beneficial in the context of Genetics education, where complex concepts often require innovative teaching methods. The success of this method suggests that such integrated approaches can significantly enhance educational outcomes and student experiences, potentially leading to improved long-term retention of scientific knowledge and increased interest in STEM fields.